SOCIAL ROLES AS PREDICTORS OF PERSONALITY CHANGE IN 15 LONGITUDINAL STUDIES OF AGING. (11th November 2018) - Graham, E K; Weston, S J; Katz, M J; Gerstorf, D; Yoneda, T B; Booth, T; Beam, C R; Petkus, A J
Abstract: The current study builds upon the coordinated integrative data analysis (IDA) of Graham et al. (under review) that replicated trajectories of change in the Big Five across 15 longitudinal studies of aging and dementia. We found consistent cross-study evidence for decreases in all traits except Agreeableness, as well as evidence for non-linear change in across the lifespan. We added retirement and marital status as predictors of linear change, and found that many studies had at least one predictor of change in each trait. When comparing predictors across study we found no evidence for replication. Results are discussed in terms of the possible randomness of significance and spurious relationships in single-study analyses, as well as the idiosyncratic role that the unshared environment may play in the context of personality development over the adult lifespan.